Successful weight loss maintenance : a systematic review of weight control registries - Luís, Catarina da Paixão (2019)
ABSTRACT - Background: Weight loss maintenance is challenging, but crucial to obtain long-term health benefits. Weight control registries identify psychological and behavioral characteristics of successful weight loss maintainers, potentially improving our understanding of this process. Objectives: To characterize the existing weight control registries and their participants, and identify correlates of weight loss maintenance. Methods: A comprehensive search of peer-reviewed articles published until November 2018 was conducted in 3 electronic databases: PubMed, Web of Science and Scopus. To be selected, studies needed to include samples from weight control registries. Results: 49 articles, corresponding to five weight control registries (United States, Portugal, Germany, Finland, and Greece), were included. Registries slightly differed on the inclusion criteria and procedures. Of 51 identified strategies, grouped in 14 domains of the Oxford Food and Activity Behaviors Taxonomy, having healthy foods available at home, regular breakfast intake, increasing vegetables’ and decreasing sugary and fatty foods’ consumption, and reducing fat in meals were the most frequently reported for weight loss and maintenance. Physical activity was the most consistent positive correlate of the magnitude of weight loss maintenance. Conclusions: To the extent of my knowledge, this is the first systematic review compiling information on weight control registries. Key characteristics were identified, which can be considered for future weight management initiatives.